Paradigma Kritis Dalam Penelitian Wacana - Suharyo Suharyo (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
So far, linguistic research, especially discourse research, is still focused on aspects of the linguistic structure as forming the discourse. Discourse is examined for the existence of cohesiveness and coherence of the discourse. What are the linguistic units that form cohesiveness and cohesiveness both lexical and grammatical coherence. This is different from discourse research using critical discourse paradigms. Critical discourse holds that discourse-forming structures are not in a social "vacuum". Because, discourse is basically a (social) action that is loaded with political, economic, power, cultural background etc. To conduct discourse research using critical paradigms, it is necessary to know the research characteristics of critical discourse analiysis, which includes (1) discourse is (social) action, (2) context, (3) historical, (4) power, (5) ideology, and ( 6) (diction) vocabulary basically (a) limits classification, (b) limits the views of a person / group, and (c) marginalizes certain people / groups. Among the available models, the critical discourse analysis model of the van Dijk model is a well-known model in Indonesia.